2020
DOI: 10.1177/1352458520928061
|View full text |Cite
|
Sign up to set email alerts
|

Higher body mass index at ages 16 to 20 years is associated with increased risk of a multiple sclerosis diagnosis in subsequent adulthood among men

Abstract: Background: Evidence for the association between body mass index (BMI) and multiple sclerosis (MS) among men remains mixed. Objective and methods: Swedish military conscription and other registers identified MS after age of 20 years and BMI at ages 16–20 years ( N = 744,548). Results: Each unit (kg/m2) BMI increase was associated with greater MS risk (hazard ratio and 95% confidence interval = 1.034, 1.016–1.053), independent of physical fitness (1.021, 1.001–1.042). Categorised, overweight and obesity were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…As previously reported, 8–10 we found excess weight/obesity during adolescence and early adulthood were associated with an increased risk of MS (after adjusting for smoking). Adjustment for other relevant MS risk factors such as genetic profile, vitamin D levels, and Epstein Barr virus antibody titers was not possible as these were not studied in this cohort at those ages.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As previously reported, 8–10 we found excess weight/obesity during adolescence and early adulthood were associated with an increased risk of MS (after adjusting for smoking). Adjustment for other relevant MS risk factors such as genetic profile, vitamin D levels, and Epstein Barr virus antibody titers was not possible as these were not studied in this cohort at those ages.…”
Section: Discussionsupporting
confidence: 86%
“…This synchronous rise in prevalence of both MS and obesity has led to a search for possible biological mechanisms underlying the association. Prospective as well as case–control studies have already shown a link between increased body mass index (BMI) in childhood and adolescence and higher risk of developing MS 8–11 …”
Section: Introductionmentioning
confidence: 99%
“…15 Infectious mononucleosis in early adulthood (20-24 years of age) has also been associated with increased MS risk, although the effect size is smaller than for IM in adolescence. 16 This study used a large population-based birth cohort in Sweden to assess the association of hospital-diagnosed IM in childhood (from birth to 10 years of age) and adolescence (11)(12)(13)(14)(15)(16)(17)(18)(19)…”
Section: Infectious Mononucleosis (Im) Is a Clinical Manifestation Of Viral Infection Predominantly Caused Bymentioning
confidence: 99%
“…This suggests that autoimmune factors may be involved in the etiology of obesity in MS. Indeed, several studies have reported an association between childhood obesity and increased risk of MS in adulthood [ 8 , 9 ]. Specifically, adipokines associated with obesity, such as leptin, adiponectin, resistin and visfatin, were suggested as possible modulators of the immune response [ 7 ].…”
Section: Introductionmentioning
confidence: 99%